The Sword-Myth Revisited - Abdulsoma, Thoarlim; Md Asadur, Rahman; Muhammadhusnee, Yanya; Makueta, Hayiwaesorhoh; Mohamad Zaharuddin, Zakaria (2017)
Islam is an incredible blend of rationality,simplicity and justice.Muslims made a personal appeal to peoples' religious consciousness and they often put forward the populistic intelligibility of Islam.Besides its simple and rational creed,Islam offers an impressive set of rituals which gained the admiration and, subsequently,the conversion of many non-Muslims to Islam.The alarming rationalism and clarity of Islam not only led the Middle East to renounce Christianity and convert to Islam in the past,it equally continues to do so with Christians in the West to the present day.But the Westerners never ceased to potray Islam as an enforcing power claiming that Islam was spread by military adventures or with the sword. They believe that non-Muslims were offered the freedom to choose between two things: Islam or death.They should know that Islam teaches that a person's faith must be pure and sincere, so it is certainly not something that can be forced on someone. Therefore,refuting their claims this paper raises questions to the Westerners who are pointing the sword to the contemporary Christians converting to Islam like Lauren Booth,Cat Stevens and the likes? Or,why the fastest growing religion is Islam in America which is believed to be the abode of the most rational people of the earth? Are American converting to Islam in fear of the sword? Or,is Dr.Zakir Nayek pointing guns to those Hindus,Christians, Buddhists and atheist who are converting to Islam after listening to his speech? So,it is all about rationality,simplicity and justice of Islam comparing to the other world religions that attract very much the rational minds.